LA INCIDENCIA DE LAS IMÁGENES MENTALES EN LA COMPRENSIÓN LECTORA EN UNA L2 - Avila López, Fco. Javier (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Recent neurobiological research points to a new direction in the study of the human mind. Mental imagery seems to be an essential condition of thought that underlies each and every act of knowledge. In light of this research, some educational approaches are incorporating the use of mental images in the classroom, in order to aid in comprehension and recall. In light of the changing conception of knowledge and, ultimately, of thought that is being brought about by neurobiological information, a study was designed at the University of Seville on the incidence of mental imagery instruction on reading comprehension in English as a foreign language. Research methodology included initial reading comprehension tests and tests on the vividness of visual imagery. A quasi-experimental investigation in accordance with the standard educational context in Andalusian secondary schools was designed. The conclusions point towards an improvement in reading comprehension in those experimental groups working with imagery.